2009
DOI: 10.1007/s00421-009-1218-z
|View full text |Cite
|
Sign up to set email alerts
|

Are there differences in running economy at different velocities for well-trained distance runners?

Abstract: The present study investigated whether there are differences in running economy at different velocities for well-trained distance runners, and to what extent a commonly used incremental protocol for measuring oxygen uptake (VO(2)) at different velocities affects the reliability of these measurements. Fifteen well-trained distance runners (9 male and 6 female) participated in this study. Gross oxygen cost of running (C (R)), heart rate (HR) and [La(-)](b) during 5-min runs at velocities ranging from 8.0 to 17 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
66
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 21 publications
11
66
1
4
Order By: Relevance
“…(2.40) applies also to running was obtained by Tam et al (2012) on top-level marathon runners from Kenya, who were able to run in submaximal condition at speeds up to 20 km h −1 (Fig. 2.13): and that it was a clear effect of C d is also demonstrated by the results of Helgerud et al (2010), who found no differences in C as a function of v h during treadmill running at similar speeds to those of Tam et al (2012).…”
Section: Energy Cost Of Locomotionsupporting
confidence: 54%
“…(2.40) applies also to running was obtained by Tam et al (2012) on top-level marathon runners from Kenya, who were able to run in submaximal condition at speeds up to 20 km h −1 (Fig. 2.13): and that it was a clear effect of C d is also demonstrated by the results of Helgerud et al (2010), who found no differences in C as a function of v h during treadmill running at similar speeds to those of Tam et al (2012).…”
Section: Energy Cost Of Locomotionsupporting
confidence: 54%
“…Running economy, measured at submaximal velocities, is representative of race velocities at distances of over 10,000 m (Helgerud, Støren, & Hoff, 2010); therefore, no change in running economy during competition should be anticipated. The unchanged step frequency and the lack of differences between observed ground reaction forces coincide with the finding that running economy remains unchanged between the sh and On conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study showed that inter-individual variability in pre-competition anxiety was considerable among the golfers. Lastly, in one study on running, inter-individual variability was also shown in the oxygen cost of running in well-trained distance runners (±7.1% in male runners and ±5.2% in female runners) (Helgerud et al, 2010). …”
Section: Introductionmentioning
confidence: 99%